Efforts Kulliyatul Mu'allimin Al-Islamiyyah (KMI) In Improving Teacher Professionalism In Pondok Modern Darussalam Gontor Ponorogo - Agus Budiman; Fata Hilman (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2018)
In an educational institution, there were goals in realizing a quality education. The quality of the school could be seen from the results of the education. Moreover, it could be seen on the quality of principals, teachers, and students. In this case, KMI's as an educational institution play an important role in increasing teacher professionalism. Therefore, the school had an effort to improve the professionalism of teachers. In this study, researchers conducted a study in Pondok Modern Darussalam Gontor after making several observations in the cottage. this institution had two activities, namely academic and non-academic. From the results, it could be found that KMI's had an effort to improve teacher professionalism such training and orientation, ta'hil,learning assignments examination of learning units, education supervision, checking achievement of targets teaching by examining student records. In addition, KMI also conducted Upgrading and Orientation by gathering new teachers and giving an understanding to the education and learning system. Learning Tasks: their application by requiring teachers to become active students and providing supporting facilities related to developing knowledge. Examination Teaching materials: require the teacher to make teaching materials that will be ratified by the teacher who serves as picket of Shaykh Diwan. Supervision in Learning: guiding the teacher from the start the teacher prepares teaching materials to how the teacher evaluates students. Checking Achievement of KBM Targets the quality of teaching and learning by examining student records: by requiring all teaching teachers to check the writing every week before the test is conducted.